👤




Zadanie 2 – Uprość wyrażenia: ( 9pkt )



a) ( - 5x – 6) + (2x – 8) =

b) (–2a– 4) + (–6a + 7) =

c) (- 2x2 – 18) + (3x2 – 9) =

d) ( 6ab –3b) + ( - ab + 2a) + (15ab + 8a – 5b) =



Zadanie 3 – Uprość wyrażenia: ( 9pkt )

a) – (9x – 5) – (x + 4) =

b) – (–5 + 2x) – (8x – 1) =

c) – (2 – 15x) – ( - 8 + 2x) =

d) - (- 6a + 3b) - ( 8ab - 6a) – (7ab + b – 5a) =


Odpowiedź :

Odpowiedź:

a) -5x-6+2x-8= -3x-14

b) -2a-4-6a+7= -8a+3

c)-2x²-18+3x²-9= x²-27

d) 6ab-3b-ab+2a+15ab+8a-5b= 20ab-8b+10a

Zad.3

a) -9x+5-x-4= -10x+1

b) 5-2x-8x+1= -10x+6

c) -2+15x+8-2x= 13x+6

d) 6a-3b-8ab+6a-7ab-b+5a= 17a-4b-15ab